Mounier–Kuhn syndrome: a tripartite analysis bridging clinical epidemiology, imaging evolution, and global research landscapes - Yanjie Wang; Luyao Wang; Haoxiang Zhang; Xiaojia Zhu; Xiaoxi Shi; Sirui Fu; Kai Sun; Jiao Wang; Quanwei Ren; Yongjin Ji; Changqing Zhao (Orphanet Journal of Rare Diseases)
Abstract Background Mounier–Kuhn syndrome (MKS) is characterized by tracheobronchomegaly with thinning or atrophy of the elastic tissue. Due to low clinical awareness, MKS is frequently overlooked on chest CT examinations, leading to diagnostic delays. This study aimed to synthesize the historical context and contemporary advancements in MKS research. Methods Five MKS cases were retrospectively identified through thoracic imaging review at our institution. A systematic review adhering to PRISMA guidelines was conducted across Web of Science (WOS) and China-specific databases (China National Knowledge Infrastructure [CNKI], Wanfang) from January 2000 to March 2025 to identify studies reporting CT-confirmed tracheobronchial dilation, to address geographic bias. Concurrently, a bibliometric analysis of WOS publications spanning January 1962 to March 2025 was performed using predefined inclusion criteria to analyze historical research trends through VOSviewer. Results Our institutional cohort (5 patients: 4 males) exhibited marked tracheobronchial dilation, with two representative cases demonstrating distinct clinical trajectories of disease progression. Systematic analysis of 147 publications encompassing 169 radiologically confirmed cases revealed significant male predominance (male-to-female ratio: 5.5:1), a mean tracheal diameter of 34.3 ± 6.1 mm, a median diagnostic delay of 3.0 years (IQR: 0.25–20.0 years), and high comorbidity prevalence including bronchiectasis (71.6%) and tracheal diverticulosis (67.5%). The most frequent clinical manifestations were cough (64.5%), dyspnoea (52.7%), and recurrent respiratory infections (57.4%). Bibliometric analysis of 288 global publications characterized research trends through country/institutional affiliations, author collaborations, journal distributions, and keyword co-occurrence, with diagnostic imaging advancements dominating recent scholarly output. Conclusions This three-phase analytical approach bridges clinical observations with global research trends, revealing significant diagnostic delays and evolving imaging paradigms in MKS management. Our findings underscore the need for enhanced clinical vigilance and multinational collaborative research initiatives to establish evidence-based therapeutic frameworks for this under-diagnosed condition.